A global history of historical demography half a century of interdisciplinarity - Fauve-Chamoux, Antoinette; Bolvan, Ioan; Sogner, Solvi (Peter Lang AG ; International Academic Publishers, 2016)
Demography, past, present and future is a common concern for all inhabitants of this planet. The variation is great, however, with regard to sources, social and political conditions, state of the art, technological development, national and local initiatives. In the course of half a century many changes take place. Keeping abreast of the gigantic streams of information and innovation in the field is demanding, even more so for a discipline with global dimensions and ambitions. The book makes fascinating reading, and preparing it has been a rewarding and thought provoking experience. The thirty-seven articles in the book represent as many different stories.